Microwave-assisted synthesis of nanorod hydroxyapatite from eggshells - Thien, Doan Van Hong; Thuyen, Nguyen Thi Bich; Quyen, Tran Thi Bich; Chiem, Nguyen Huu; Thuy, Van Pham Dan; Viet, Pham Hung (Vietnam Journal of Science, Technology and Engineering, 2021)
Nanorod hydroxyapatite (HA) was synthesised from eggshells by using a microwave-assisted technique. In recent years, hydroxyapatite [HA, Ca10(PO4)6(OH)2] has gained attention because it exhibits excellent biocompatibility with soft tissues, such as muscle, gums, and skin. Every day, millions of tonnes of eggshells are generated around the world as bio-waste. The eggshell occupies about 11% of the total weight of an egg, and it consists of calcium carbonate (94%), calcium phosphate (1%), magnesium carbonate (1%), and organic matter (4%) (protein fibres). With eggshells and phosphoric acid as precursors, the reaction was carried out in a microwave with an irradiation power of 800 W for 45 minutes. The effects of Ca/P molar ratiosandthepower ofmicrowaveswereinvestigated. The obtained hydroxyapatite was characterised by X-ray diffraction (XRD), scanning electron microscope (SEM), and infrared spectroscopy (IR). During this research, HA nanorods were successfully synthesised from eggshells and phosphoric acid as precursors using microwave-assisted technology. The nanorod-like HA samples were 20-40 nm in diameter and 130-180 nm in length.